Kewenangan Hakim Mahkamah Konstitusi dalam Memanggil Menteri sebagai Pemberi Keterangan pada Perkara Perselisihan Hasil Pemilihan Umum Presiden dan Wakil Presiden Tahun 2024 - Wibowo, Renaldy Wijaksana; Saputro, Bayu (Universitas Batanghari Jambi, 2025)
In the 2024 Presidential PHPU trial, the Constitutional Court summoned four Ministers to give testimony in the trial. This raises a problem, because in the PMK PHPU President there is not a single provision that explicitly authorizes the Constitutional Court judge to be able to summon the informant. This study aims to firstly, determine the legal basis for the authority of Constitutional Court judges to summon the informant in the PHPU Presidential Election Case. Second, to find out the consequences caused by the summoning of the informant by the Constitutional Court judges in the PHPU Presidential Election Case. Third, to find out the clarity of the regulation regarding the informant in PMK No. 4/2023 and to provide a concept of the necessary arrangements in order to avoid abuse of authority by the Constitutional Court judges in the PHPU President. This paper uses normative legal research, using a statutory approach and a case approach. Based on the results of the research, it turns out that there is no authority for Constitutional Court judges to summon the informant because this is not explicitly regulated in the PMK PHPU President. The unclear legal basis governing the summoning of the informant in the Presidential PHPU trial and the actions of Constitutional Court judges who summon the informant on their own initiative can cause problems. The problems that arise relate to potential violations of the principle of independence and the emergence of legal uncertainty. There is ambiguity in the authority to summon the informant in the Presidential PHPU trial. Therefore, further regulation is needed regarding the authority to summon the informant in the PHPU Presidential Election case so that there is a clear division of authority in order to present the informant at the trial.